Biliary sphincterotomy reduces the risk of acute gallstone pancreatitis recurrence in non-candidates for cholecystectomy. Issue 11 (November 2019) - García de la Filia Molina, Irene; García García de Paredes, Ana; Martínez Ortega, Antonio; Marcos Carrasco, Natalia; Rodríguez De Santiago, Enrique; Sánchez Aldehuelo, Rubén; Foruny Olcina, Jose Ramón; González Martin, Juan Ángel; López Duran, Sergio; Vázquez Sequeiros, Enrique; Albillos, Agustín
Abstract: Background: Population aging and comorbidity are leading to an increase in patients unfit for cholecystectomy. Aims: To evaluate whether endoscopic biliary sphincterotomy after a first episode of acute gallstone pancreatitis reduces the risk of pancreatitis recurrence and gallstone-related events in non-surgical candidates. Methods: Retrospective study of patients admitted for a first episode of acute gallstone pancreatitis rejected for cholecystectomy between 2013–2018. The role of endoscopic sphincterotomy was evaluated by adjusting for age, severity of pancreatitis, and presence of choledocholithiasis. Results: We included 247 patients (mean age 80 ± 12 years; Charlson index: 5; severity of pancreatitis: 72% mild). Sphincterotomy was performed in 23.9%. Recurrence of pancreatitis occurred in 17.4% patients (median follow-up: 426 days). The one-year cumulative incidence of a new episode of pancreatitis was 1.8% (95% confidence interval [CI]: 0.2–12%) and 23% (95% CI: 17–31%) in patients with and without sphincterotomy, respectively (p = 0.006). In multivariate analysis, sphincterotomy showed a protective role for recurrence of pancreatitis (adjusted hazard ratio [HR]: 0.29, 95% CI: 0.08–0.92, p = 0.037) and for any gallstone-related event (HR 0.46, 95% CI: 0.21–0.98, p = 0.043). Conclusions: Endoscopic biliary sphincterotomy reduced the risk of gallstone pancreatitis recurrence and other biliary-related disorders in patients with a first episode of pancreatitis non-candidates for cholecystectomy.